2010
DOI: 10.1007/s12011-010-8688-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal (Hg, Cr, Cd, and Pb) Contamination in Urban Areas and Wildlife Reserves: Honeybees as Bioindicators

Abstract: The degree of heavy metal (Hg, Cr, Cd, and Pb) pollution in honeybees (Apis mellifera) was investigated in several sampling sites around central Italy including both polluted and wildlife areas. The honeybee readily inhabits all environmental compartments, such as soil, vegetation, air, and water, and actively forages the area around the hive. Therefore, if it functions in a polluted environment, plant products used by bees may also be contaminated, and as a result, also a part of these pollutants will accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 8 publications
5
93
1
8
Order By: Relevance
“…The lowest Hg content was found as 1.125 ppm in the Ghorveh samples. Perugini et al (2011) did not demonstrate Hg presence in honeybee samples. In principle, the pollutants can be accumulated in soil and plants (Spodniewska, 2007), and are collected by bees along with nectar and pollen (Roman, 2004;Roman, 2009).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The lowest Hg content was found as 1.125 ppm in the Ghorveh samples. Perugini et al (2011) did not demonstrate Hg presence in honeybee samples. In principle, the pollutants can be accumulated in soil and plants (Spodniewska, 2007), and are collected by bees along with nectar and pollen (Roman, 2004;Roman, 2009).…”
Section: Discussionmentioning
confidence: 76%
“…There are a few publications dealing with honeybees and metal pollution (Crane, 1984, Porrini et al, 2003Perugini et al, 2011). In the current research, the highest concentration of Hg was measured as 4.786 ppm in the samples from Kamyaran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio-indication of plant pathogens is a small field limited to Erwinia amylovora. (Perugini et al, 2011). The incidence of pesticides and heavy metals over a threeyear study (2008)(2009)(2010) in natural reserves in the Marche region in Italy has been studied in live be es, dead bees and honey.…”
Section: State Of the Art Bio-indication With Honeybee Coloniesmentioning
confidence: 99%
“…Therefore, in bio-indication studies only significant e xceeded concentrations of metals in honeybees studied under defined site conditions, indicate an extra exposure of bees to heavy metals and may draw attention for further studies. Concentrations of heavy metals show significant temporal and spatial variation (Lambert et al, 2012 b ;Perugini et al, 2011;Ruschioni et al, 2013;Satta et al, 2012;. Bio-indication studies revealed that high heavy metal concentrations can only be detected in live honeybees and not in honey and dead bees (Ruschioni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%